Majority rule, minority issues: The Macedonian question in the Dekemvriana. Issue 1 (2nd January 2017) - Horncastle, James
ABSTRACT: This article examines the role of the Macedonian Question in the 1944 December Uprising ( Dekemvriana ) in Greece. While the Dekemvriana is commonly portrayed in right–left terminology in the historiography, this article argues that part of the reason for the left's failure was their inability to manage the Macedonian ethnic component of the struggle, either within their armed forces or in their relationship with Yugoslavia. As such, this article integrates the early phases of the Greek Civil War into the broader literature on minorities in civil conflict, while simultaneously exposing some of the myths about Macedonian involvement that result from its contemporary political ramifications.